Squint - Morris, Chad; Brown, Shelly, 1979- (Shadow Mountain, 2019)
Flint Minett has keratoconus, an eye disease that could eventually make him blind, but desperately wants to win a comic book art contest so that he and his new friend McKell Panganiban will be better accepted at middle school. Through a series of challenges, the two friends learn how to trust each other, believe in themselves, and see what really matters.